Core@Satellite Janus Nanomotors with pH‐Responsive Multi‐phoretic Propulsion. (6th July 2020) - Xing, Yi; Zhou, Mengyun; Xu, Tailin; Tang, Songsong; Fu, Yang; Du, Xin; Su, Lei; Wen, Yongqiang; Zhang, Xueji; Ma, Tianyi
Abstract: We report core@satellite Janus mesoporous silica‐Pt@Au (JMPA) nanomotors with pH‐responsive multi‐phoretic propulsion. The JMPA nanomotors first undergo self‐diffusiophoretic propulsion in 3.0 % H2 O2 due to the isolation of the Au nanoparticles (AuNPs) from the PtNPs layer. Then the weak acidity of H2 O2 can trigger the disassembly and reassembly of the AuNPs, resulting in the Janus distribution of large AuNPs aggregates. Such reconstruction of JMPA leads to the contact between PtNPs and AuNPs aggregates, thus changing the propulsion mechanism to self‐electrophoresis. The asymmetric and aggregated AuNPs also enable the generation of a thermal gradient under laser irradiation, which propels the JMPA nanomotors by self‐thermophoresis. Such multi‐phoretic propulsion offers considerable promise for developing advanced nanomachines with a stimuli‐responsive switch of propulsion modes in biomedical applications. Abstract : Multi‐phoretic propulsion : pH‐responsive core@satellite Janus‐mesoporous silica/Pt@Au nanomotors can transform their phoretically driven mechanisms in acidic H2 O2 solution from initial self‐diffusiophoresis to self‐electrophoresis after the disassembly and reassembly of Au nanoparticles, then to self‐thermophoresis upon laser illumination.